2017
DOI: 10.1371/journal.pone.0185687
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtype specific efficacy of MEK inhibitors in pancreatic cancers

Abstract: Pancreatic cancer is an increasing cause of cancer related death worldwide. KRAS is the dominant oncogene in this cancer type and molecular rationale would indicate, that inhibitors of the downstream target MEK could be appropriate targeted agents, but clinical trials have failed so far to achieve statistically significant benefit in unselected patients. We aimed to identify predictive molecular biomarkers that can help to define subgroups where MEK inhibitors might be beneficial alone or in combination. Next-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…As a KRAS mutated cell line, survival mechanisms are upregulated per se in Panc1 cells involving elevated Akt expression and activation [ 53 ]. In line with earlier studies by other groups, we also confirmed relatively high activated p-Akt/Ser473 levels in Panc1 cells using flow cytometry [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a KRAS mutated cell line, survival mechanisms are upregulated per se in Panc1 cells involving elevated Akt expression and activation [ 53 ]. In line with earlier studies by other groups, we also confirmed relatively high activated p-Akt/Ser473 levels in Panc1 cells using flow cytometry [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Activating mutations in Kras promote proliferation and survival through the RAF/MEK/ERK and PIK3/AKT pathways. Kras G12D mutations, as investigated in our study, are the most prevalent mutations in pancreatic cancer [46], but due to the inherent nature of the Ras protein, Ras inhibition has not resulted in relevant clinical benefit despite high prevalence of Ras mutations in pancreatic cancer. Therefore, therapies designed to specifically target downstream effectors have been developed (reviewed in [47]).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting PDAC tumors with inhibitors of MEK, such as trametinib, has shown efficacy in pre-clinical models of PDAC, 10 , 11 although resistance is a frequent occurrence and toxicity issues have also resulted in limited success in clinical trials. 12 Inhibitors of Src homology region 2 (SH2)-containing protein tyrosine phosphatase 2 (SHP2) have been shown to prevent adaptive resistance to MEK inhibitors in multiple cancer models, 13 , 14 and combinations of ERK and autophagy inhibitors have also demonstrated enhanced efficacy compared to single-agent treatments.…”
Section: Introductionmentioning
confidence: 99%